The truth about bears - Eaton, Maxwell, III (Roaring Brook Press, 2018)
Did you know that polar bears smell seals through the ice and snow in order to find and eat them? Did you know that when a bear is born, it weighs less than a picture book? Did you know that bears sleep all winter and don't go to the bathroom while they hibernate?